2016
DOI: 10.1080/17425247.2016.1256283
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative usability study for a certolizumab pegol autoinjection device in patients with rheumatoid arthritis

Abstract: Objectives: To compare the usability of a new certolizumab pegol (CZP) autoinjector with the adalimumab, etanercept, and golimumab devices in patients with rheumatoid arthritis. Methods: Two identical studies were performed in 2013 and 2016; patients performed a simulated selfinjection with the CZP autoinjector and the most up-to-date device versions at the time in a randomized, consecutive sequence. The primary end point was the ranking of the four autoinjectors in order of preference. Device usability and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…Knowledge about use errors of existing, similar equipment is an important source of information on the design and development of new medical devices. A proper analysis of known problems is essential for ensuring that (Jeannerot et al, 2016) Buttons (Fujioka et al, 2015;Rohrer et al, 2013) Feedback -audible (Lange et al, 2015;Varunok et al, 2011) Feedback -visible (Lange et al, 2015;Lange et al, 2014) Packaging (Guerlain et al, 2010b) Safety cap (Lange et al, 2015;Pachon et al, 2014;Demary et al, 2014;Domańska et al, 2017;Guerlain et al, 2010b) Site disinfection (Jeannerot et al, 2016) Washing hands (Jeannerot et al, 2016) these issues will not occur with a newly developed device. One of the strengths of the present study is its systematic analysis of all use errors reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Knowledge about use errors of existing, similar equipment is an important source of information on the design and development of new medical devices. A proper analysis of known problems is essential for ensuring that (Jeannerot et al, 2016) Buttons (Fujioka et al, 2015;Rohrer et al, 2013) Feedback -audible (Lange et al, 2015;Varunok et al, 2011) Feedback -visible (Lange et al, 2015;Lange et al, 2014) Packaging (Guerlain et al, 2010b) Safety cap (Lange et al, 2015;Pachon et al, 2014;Demary et al, 2014;Domańska et al, 2017;Guerlain et al, 2010b) Site disinfection (Jeannerot et al, 2016) Washing hands (Jeannerot et al, 2016) these issues will not occur with a newly developed device. One of the strengths of the present study is its systematic analysis of all use errors reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…"Incorrect handling" refers to errors where users did not perform actions with the correct finger (Salter et al, 2014) or the correct hand (Hudry et al, 2017). The "incorrect storage" subcategory is related to cases in which users could not state the correct storage conditions for the auto-injection device (Sicherer et al, 2000;Domańska et al, 2017) or did not take the device out of the refrigerator long enough before the injection to reach room temperature (Schiff et al, 2016). With regard to post-injection tasks, three publications mentioned failure to massage the injection site after the injection (Salter et al, 2014;Brown et al, 2013;Saleh-Langenberg et al, 2017).…”
Section: Categories Of Identified Use Errors and Close Callsmentioning
confidence: 99%
See 3 more Smart Citations